METODE PENYULUHAN PERTANIAN DAN PRODUKTIVITAS PADI SAWAH DI KELURAHAN BARUGA KECAMATAN BARUGA KOTA KENDARI - Hikmah Rahmizani; Dasmin Sidu; Sukmawati Abdullah (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
The objective of this study is to ascertain the most effective cultivation techniques and yield potential of paddy rice in the Baruga subdistrict of Kendari City. The study population consisted of all rice paddy farmers in the Baruga subdistrict of Kendari City, numbering 287 individuals. The sample size was determined using the Slovin formula with an error rate of 20%, resulting in a sample of 34 respondents. The research sample was selected using the simple random sampling method. Data were collected through observation, interviews, and document analysis, with the assistance of media in the form of questionnaires. The variables under investigation in this study were agricultural extension methods and the productivity of paddy rice farming. The data were analyzed using descriptive statistics to identify the most effective agricultural extension method and to determine the optimal productivity formula for paddy rice farming in Baruga Village. The results demonstrated that the agricultural extension methods conducted by extension workers in Baruga Village, Kendari City, were primarily classified into three categories: anjangsana, demonstration, and internet extension methods. The demonstration method, encompassing both plot and method demonstrations, was the most prevalent and well-received among wet-rice farmers. The average productivity of paddy rice in Baruga Subdistrict, Kendari City, in 2023 was 4.34 tons/ha.